The Boundedness on Mixed Hardy Spaces - Wei Ding; Meidi Qin; Yueping Zhu (Journal of Function Spaces)
The boundedness of operators on Hardy spaces is usually given by atomic decomposition. In this paper, we obtain the boundedness of singular integral operators in mixed Journé class on mixed Hardy spaces by a direct method.